2020
DOI: 10.1186/s13287-020-01994-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of adipose-derived stem cells in photoaging: basic science and literature review

Abstract: Photoaging is mainly induced by continuous exposure to sun light, causing multiple unwanted skin characters and accelerating skin aging. Adipose-derived stem cells(ADSCs) are promising in supporting skin repair because of their significant antioxidant capacity and strong proliferation, differentiation, and migration ability, as well as their enriched secretome containing various growth factors and cytokines. The identification of the mechanisms by which ADSCs perform these functions for photoaging has great po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 173 publications
(174 reference statements)
0
39
0
1
Order By: Relevance
“…Several findings have shown that F-GRF and related AD-MSCs/SVF are effective in treating soft tissue defects and wrinkles [ 11 , 20 , 21 , 22 , 23 ], and previous studies have emphasized their application in wound healing (WH), scars treatment (ST), and also in the treatment of radiotherapy damage [ 24 ]. Thanks to the therapeutic effects of AD-MSCs and SVF in WH and ST, great attention has been paid to utilizing AD-MSCs in the treatment of photoaging damage.…”
Section: The Protective Role Of Ad-mscs In Skin Photoaging: In Vitro and In Vivo Analysismentioning
confidence: 99%
“…Several findings have shown that F-GRF and related AD-MSCs/SVF are effective in treating soft tissue defects and wrinkles [ 11 , 20 , 21 , 22 , 23 ], and previous studies have emphasized their application in wound healing (WH), scars treatment (ST), and also in the treatment of radiotherapy damage [ 24 ]. Thanks to the therapeutic effects of AD-MSCs and SVF in WH and ST, great attention has been paid to utilizing AD-MSCs in the treatment of photoaging damage.…”
Section: The Protective Role Of Ad-mscs In Skin Photoaging: In Vitro and In Vivo Analysismentioning
confidence: 99%
“…Pajanan radiasi ultraviolet dari matahari merupakan faktor utama penuaan ekstrinsik sehingga disebut photo aging yang mengacu pada efek pajanan sinar ultraviolet dalam waktu lama. 3 Pada penuaan ekstrinsik lapisan epidermis menebal, sedangkan pada penuaan intrinsik, lapisan epidermis menipis. Stratum korneum menebal karena kegagalan degradasi korneosit dari desmosom.…”
Section: Penuaan Ekstrinsikunclassified
“…In several reports, stem cell therapy has been proven to accelerate skin repair and the wound healing process. Out of all stem cell agents, ADSCs are the most commonly used stem cell therapeutics, and their use in tissue regeneration and skin rejuvenation has been extensively studied [97,98]. Although ADSCs' ability to multi-differentiate contributes to their therapeutic efficacy, paracrine effects of ADSCs are noted as the key mechanisms in tissue repair by modulating the local microenvironment.…”
Section: Theranostic/cosmetic Applications Of Extracellular Vesicles For Skin Agingmentioning
confidence: 99%